SWOT Analysis in Improving Service to the Community in Jepara Kelurahan Surabaya City - Hermien Tridayanti; Febri Yuriperka (NAROTAMA UNIVERSITY, Indonesia, 2022)
The purpose of the study was to determine the quality of public services at the Jepara sub-district office, Bubutan sub-district, Surabaya and to determine the factors that influence the quality of public service at the Jepara sub-district office, Bubutan sub-district, Surabaya. Descriptive qualitative data analysis to provide an overview of the research problem. In data collection, the methods used are observation, interviews, and documentation. This research was conducted at the Jepara Sub-District Office using SWOT, because by using SWOT, the Jepara Sub-District office can identify and determine the strengths, weaknesses, opportunities, and threats at the Jepara Sub-District office which aims to determine the condition of the Jepara Sub-District office by maximizing the strengths (Strengths). ) and opportunities (Opportunities), but can also face weaknesses (Weaknesses) and threats (Threats). In the SWOT analysis that has been carried out at the Jepara Kelurahan office, it can be seen that the Jepara Kelurahan office is included in the quadrant 1 strategy which means it supports an aggressive strategy, therefore in organizational development that will have a very large opportunity, so this can be a good consideration for the Kelurahan. Japan. Implementation in the development of this SWOT analysis is to improve public services at the Jepara Village office.